A Review of Cancer Genetics and Genomics Studies in Africa - Rotimi, Solomon O.; Rotimi, Oluwakemi A.; Salhia, Bodour (Frontiers in Oncology, 2021)
Cancer is the second leading cause of death globally and is projected to overtake infectious disease as the leading cause of mortality in Africa within the next two decades. Cancer is a group of genomic disease that presents with intra- and inter-population unique phenotypes, with Black populations having the burden of morbidity and mortality for most types. At large, the prevention and treatment of cancers have been propelled by the understanding of the genetic make-up of the disease of mostly non-African populations. By the same token, there is a wide knowledge gap in understanding the underlying genetic causes of and genomic alterations associated with cancer among black Africans. Accordingly, we performed a review of the literature to survey existing studies on cancer genetics/genomics and curated findings pertaining to publications across multiple cancer types conducted on African populations. We used PubMed MeSH terms to retrieve the relevant publications from 1990 to December 2019. The metadata of these publications were extracted using R text mining packages, RISmed, and Pubmed.mineR. The data showed that only 0.329% of cancer publications globally were on Africa, and only 0.016% were on cancer genetics/genomics from Africa. Although the most prevalent cancers in Africa are cancers of the breast, cervix, uteri, and prostate, publications representing breast, colorectal, liver, and blood cancers were the most frequent in our review. The most frequently reported cancer genes were BRCA1, BRCA2, and TP53. Next, the genes reported in the abstracts of the reviewed publications were extracted and annotated into 3 gene ontology classes. Genes in the cellular component class were mostly associated with cell part and organelle part, while those in biological process and molecular function classes were mostly associated with cell process, biological regulation, and binding; catalytic activity, respectively. This review highlights the paucity of research on cancer genomics on African populations, identified the gaps, and discussed the need for concerted efforts to encourage more research on African cancer genomics.